Challenges in Designing English Materials for ESP Students: Insights from EFL Undergraduates - Hamid, Faishal Hamdan Syakirin; Fauzi, Florence Angelaila; Hafizah, Azizatun; Qamariah, Zaitun (Pusat Kajian Bahasa Daerah & Budaya, 2025)
This study explores the challenges faced by undergraduate English Education students in designing English for Specific Purposes (ESP) materials. ESP material design requires the integration of field-specific content with general language skills that are contextually relevant. Using a qualitative descriptive approach, data were collected through semi-structured interviews with five students who have experience in designing ESP materials. Thematic analysis revealed that students face challenges in needs analysis, content selection, and technology integration. Limited resources, such as time and technological infrastructure, also posed significant obstacles. Strategies employed to overcome these challenges include collaboration with peers and lecturers, adaptation of existing materials, and utilizing online resources. This study highlights the importance of language simplification and feedback-based evaluation to ensure the relevance and effectiveness of ESP materials. The findings contribute to curriculum development and ESP teaching practices by emphasizing collaborative approaches and strategic use of technology.